Implementasi Ketahanan Kesehatan Nasional: Studi Kasus Pelaksanaan Program Inovasi Bidang Kesehatan di Provinsi DKI Jakarta - Kirana, Septy Zahrawi; Ascobat Gani, Ascobat Gani; Lukman Hakim, Lukman Hakim (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
The purpose of this study is to thoroughly review and analyze the development and implementation of innovation programs in the Provincial Health Office. This study uses a qualitative method with depth interview and secondary data review. This study has shown that innovation has been a necessity that has been conducted routinely in the Health Office. The innovation performance indicators have been achieved and become one of the supporting factors for innovation, aside from public demands. The Health Office’s policies to promote innovation need further evaluation and improvement, hence able to strengthen the health system and achieve national health resilience.